Respuesta :

Here is an example of how to do the work :)

Step-by-step explanation:

Simplify the following algebraic expressions.

   - 6x + 5 + 12x -6

   2(x - 9) + 6(-x + 2) + 4x

   3x2 + 12 + 9x - 20 + 6x2 - x

(x + 2)(x + 4) + (x + 5)(-x - 1)

1.2(x - 9) - 2.3(x + 4)

(x2y)(xy2)

(-x2y2)(xy2)

Group like terms and simplify.

- 6x + 5 + 12x -6 = (- 6x + 12x) + (5 - 6)

= 6x - 1

Expand brackets.

2(x - 9) + 6(-x + 2) + 4x = 2x - 18 - 6x + 12 + 4x

Group like terms and simplify.

= (2x - 6x + 4x) + (- 18 + 12) = - 6

Group like terms and simplify.

3x2 + 12 + 9x - 20 + 6x2 - x

= (3x2 + 6x2) + (9x - x) + (12 - 20)

= 9x2 + 8x - 8

Expand brackets.

(x + 2)(x + 4) + (x + 5)(- x - 1)

= x2 + 4x + 2x + 8 - x2 - x - 5x - 5

Group like terms.

= (x2 - x2) + (4x + 2x - x - 5x) + (8 - 5)

= 3

Answer:1 solution

Step-by-step explanation: